Iban women and side-income generation in Bintulu - Rosli, Anita; Daud, Adrian; Md Saad, Juniza (Human Resource Management Academic Research Society, 2021)
Like other women, Iban women do several activities as the side-income generation to support family life such as farming, handicraft making, and traditional food processing and business. This study aims to investigate the involvement of Iban women in the side-income generation in Bintulu, Sarawak. Thus, the target population in this study is Iban women who are involved in side-income activities only as not all Iban women in Bintulu involve in side-income activities. This study will identify the type of side-income activities and find out barriers to women's participation in side-income activities and propose relevant solutions to the problems. The questionnaire will be distributed to the target population and descriptive data analysis will be used to describe and summarize the findings. From the findings of the study, the researcher will come out with relevant suggestions to reduce and solve problems faced by Iban women in the side-income generation. For instance, propose appropriate programs and training to enhance their knowledge and skills in side-income activities that they preferred. Side-income generation among Iban women not only benefits the family but will create positive effects on Iban women development and empowerment in Sarawak generally.